Phenotypic plasticity in response to environmental heterogeneity contributes to fluctuating asymmetry in plants: first empirical evidence. (28th November 2017) - Tucić, Branka; Budečević, Sanja; Manitašević Jovanović, Sanja; Vuleta, Ana; Klingenberg, Christian Peter
Abstract: Fluctuating asymmetry (FA) is widely used to quantify developmental instability (DI) in ecological and evolutionary studies. It has long been recognized that FA may not exclusively originate from DI for sessile organisms such as plants, because phenotypic plasticity in response to heterogeneities in the environment might also produce FA. This study provides the first empirical evidence for this hypothesis. We reasoned that solar irradiance, which is greater on the southern side than on the northern side of plants growing in the temperate zone of the Northern Hemisphere, would cause systematic morphological differences and asymmetry associated with the orientation of plant parts. We used geometric morphometrics to characterize the size and shape of flower parts in Iris pumila grown in a common garden. The size of floral organs was not significantly affected by orientation. Shape and particularly its asymmetric component differed significantly according to orientation for three different floral parts. Orientation accounted for 10.4% of the total shape asymmetry within flowers in the falls, for 11.4% in the standards and for 2.2% in the style branches. This indicates that phenotypic plasticity in response to a directed environmental factor, most likely solar irradiance, contributes to FA of flowers under natural conditions. That FA partly results from phenotypic plasticity and not just from DI needs to be considered by studies of FA in plants and other sessile organisms.